Age-Related Differences in Motivation of Recreational Runners, Marathoners, and Ultra-Marathoners - Gerasimuk, Dagmara; Malchrowicz-Mośko, Ewa; Stanula, Arkadiusz; Bezuglov, Eduard; Achkasov, Evgenij; Swinarew, Andrzej; Waśkiewicz, Zbigniew (Frontiers in Psychology, 2021)
Aim: This study was aimed to investigate the influence of age on the motivations of various types of runners: marathoners, ultra-marathoners, and non-starters. Methods: A total of 1,537 runners including 380 women (24.7%) and 1,157 men (75.3%) took part in the diagnostic survey and completed the motivations of marathoners’ scales questionnaire (MOMS). The effect sizes were estimated. Results: The article presents several statistically significant differences in the impact of age on the motivations of runners in different categories and compares the motivations of marathon runners, ultramarathon runners, and non-starters. The results show that young non-starters decide to run for personal goal achievement, and for both marathon and ultramarathon runners, recognition and competition are important. However, for older people in all groups (non-starters, marathoners, and ultramarathoners), personal goal achievement is of the least importance. Among the oldest runners, the most important motives were self-esteem for non-starters and health orientation for marathoners and for ultramarathoners.